(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
The increase in trend of medical negligence lawsuits against doctors due to awareness among general population because of various factors has lead to increase anxiety among medical professionals. Knowledge about medico-legal issues, laws relating to medical practice and medical ethics, which were not taken seriously earlier by the health professionals, has made them more vulnerable to litigations. All these issues are taught to them in their second year of undergraduate training, but the lack of understanding of these issues during their internship training made them inadequate with respect to standards of noble medical profession. Hence, the present study was conducted to evaluate the knowledge and awareness of our interns on handling routine medico-legal issues in the wards and casualty. A total of 100 interns posted in various departments of the institute participated in this research. Data were collected in the form of a self-administered questionnaire comprising close-ended questions related to the topic of the study. The majority of participants had knowledge about bulk of medico-legal issues. However, there was uncertainty regarding preparation of injury certificate, hospital indemnity insurance, medical record preservation and evidence collection in sexual assault and poisoning cases. The knowledge gaps identified through this study on particular topics help us to plan some remedial measures in undergraduate and internship training.